2023
DOI: 10.1097/inf.0000000000004002
|View full text |Cite
|
Sign up to set email alerts
|

Long Duration of Oral Care Using Mother’s Own Milk Influences Oral Microbiota and Clinical Outcomes in Very-low-birthweight Infants: Randomized Controlled Trial

Abstract: Background: Several studies have focused on the clinical outcomes of oral care using colostrum for a limited time (2–5 days) in very-low-birthweight (VLBW) infants. However, the effect of long-term mother’s own milk (MOM) on the clinical outcomes and oral microbiota of VLBW infants remains unknown. Methods: In this randomized controlled trial, VLBW neonates were randomly assigned to oral care by MOM or sterile water (SW) groups until they started oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The results of this study showed that there was no statistically significant difference between the Shannon Index and Simpon Index of the oral microbiota in the experimental and control groups within 21 days after birth, and the beta diversity was not statistically different. The results of Thatrimontrichai et al 28 were similar to this study. Therefore, we hypothesize that administration of oropharyngeal milk has no effect on the structure and diversity of the early oral microbiota in very low birth weight infants.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study showed that there was no statistically significant difference between the Shannon Index and Simpon Index of the oral microbiota in the experimental and control groups within 21 days after birth, and the beta diversity was not statistically different. The results of Thatrimontrichai et al 28 were similar to this study. Therefore, we hypothesize that administration of oropharyngeal milk has no effect on the structure and diversity of the early oral microbiota in very low birth weight infants.…”
Section: Discussionsupporting
confidence: 90%